Big data : principles and paradigms - Buyya, Rajkumar, 1970-; Calheiros, Rodrigo N.; Vahid Dastjerdi, Amir (Cambridge, MA : Morgan Kaufmann is an imprint of Elsevier, 2016)
Big Data: Principles and Paradigms captures the state-of-the-art research on the architectural aspects, technologies, and applications of Big Data. The book identifies potential future directions and technologies that facilitate insight into numerous scientific, business, and consumer applications. To help realize Big Data's full potential, the book addresses numerous challenges, offering the conceptual and technological solutions for tackling them. These challenges include life-cycle data management, large-scale storage, flexible processing infrastructure, data modeling, scalable machine learning, data analysis algorithms, sampling techniques, and privacy and ethical issues.
Part I. Big data science -- part II. Big data infrastructures and platforms -- part III. Big data security and privacy -- part IV. Big data applications.
Online resource; title from PDF title page (ScienceDirect, viewed July 11, 2016).
Includes bibliographical references and index.
Keywords: Big data; COMPUTERS -- Data Processing; Big data; Electronic books